Determinants of survival in gastric cancer: A single center experience - Doğan, Fadlı; Dincer, Mürşit; Karabulut, Koray (My University, 2019)
Aim: Gastric cancer is the second leading cause of cancer deaths worldwide. The effect of lymph node dissection and the extent of gastric resection on survival remains controversial, while improved survival has been reported with combined chemotherapy and radiotherapy. In this study, we aimed to present a single center experience.Material and Methods: Patients undergoing gastric resection due to gastric cancer were retrospectively assessed in order to examine the determinants of survival in gastric adenocarcinoma. Gastric malignancies other than adenocarcinoma were excluded from the study. Result of preoperative diagnostic work up, operative data, histopathology of the surgical specimen, and postoperative follow up parameters were evaluated and recorded.Results: Among a total of 139 patients operated due to gastric malignancy between January 2008 and January 2014 in our unit, 124 were diagnosed with an adenocarcinoma. The median duration of follow up was 6 months, during which 53 patients (42.7%) were found to have disease recurrence (10 local, and 43 systemic). A higher T stage was associated with shorter survival (p<0.0001), as was the N stage (p<0.0001). Parameters that emerged as having a statistical significance (p<0.05) in the univariate analysis, i.e. gender, tumor size, T stage, N stage, differentiation, and surgical margin status, were subjected to a multivariate analysis, where T stage, N stage, and proximal/distal surgical margin status maintained their significant association with the survival.Conclusion: Several factors such as tumor stage, tumor diameter, histological type, and number of metastases emerged as having significant prognostic importance in patients with gastric cancer.
Keywords: Genel ve Dahili Tıp; Patoloji; Onkoloji